Multimedia Interaktif Edugame Star: Solusi untuk Meningkatkan Numerasi Anak Usia Dini - Sholihah, Imroatus; Wijaya, Intan Prastihastari; Lestariningrum, Anik (Universitas Nusantara PGRI Kediri, 2025)
Numeracy skills play a crucial role in daily life, including for early childhood. Based on initial observations at Putera Bhakti Kindergarten, it was found that there was a problem of low numeracy skills and lack of stimulation provided by teachers, so researchers applied Edugame Star media to improve early childhood numeracy skills. This study aims to create the effect of the application of interactive multimedia Edugame Star in improving early childhood numeracy skills and analyzing the differences with conventional learning media. Researchers chose a quantitative descriptive research method with a pseudo-experimental approach and Posttest-only design with nonequivalent groups to conduct the proof. The population in the study included all students at Putera Bhakti Kindergarten with 2 sample groups, including the experimental group (B3) and the control group (B1). The results of the study based on the Mann U Whitney Test showed that the value of Exact Sig. [2*(1-tailed Sig.)] of 0,009<0,05, then H0 is rejected, which means that there is an effect of the application of interactive multimedia Edugame Star on early childhood numeracy skills. The research results also showed a difference in the value of the mean rank results, namely the control group reached 13.97 and the experimental group 23.03 which resulted in a difference of 9.06. This significant difference causes H0 to be rejected, which means that there is a difference in the application of interactive multimedia Edugame Star with the application of conventional media.